2019
DOI: 10.33314/jnhrc.v16i41.1673
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis as a Predictor of Serious Bacterial Infection in Febrile Infants

Abstract: Background: Most of the febrile infants <90 days old will have no more than a mild viral infection but there is a substantial minority that will be diagnosed as having serious bacterial infection at a reported prevalence of 10–14%. A simple, readily available, inexpensive diagnostic marker that yields results quickly and also accurately identifies bacterial infections in febrile infants would be of great value in management of these infants. This study aims to assess the role of thrombocytosis in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Elevated platelet levels have been reported in infections. Mishra et al showed that severe bacterial infections were characterized by high platelet count levels [ 37 ]. Moreover, Harris et al found that increased levels of circulating thrombocytes could be a marker of surgical site infection in subjects that have undergone head and neck surgery [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated platelet levels have been reported in infections. Mishra et al showed that severe bacterial infections were characterized by high platelet count levels [ 37 ]. Moreover, Harris et al found that increased levels of circulating thrombocytes could be a marker of surgical site infection in subjects that have undergone head and neck surgery [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased platelet count could predict poor efficacy of 3 rd GC in this study. Mishra et al [ 20 ] found that thrombocytosis can be used to predict severe bacterial infection, and Johansson et al [ 21 ] proposed that some gram-positive bacteria can induce platelet activation and aggregation. In this study, SBP patients with higher platelet counts were more likely to have no response to 3 rd GC, which might be because increased platelets represent serious infection and gram-positive bacterial infection.…”
Section: Discussionmentioning
confidence: 99%